Methods of Prevention and Control of German and Brown-banded Cockroaches in Human Habitats: A Systematic Review - Mehdi Khoobdel; Hossein Dehghan; Seyed Hassan Nikookar; Mohammad Moradi (Mazandaran University of Medical Sciences, 2021)
Introduction and Objectives: Cockroaches cause food spoilage, mechanical transmission of pathogens, psychological anxiety, and allergic respiratory reactions in humans due to their high adaptation and rapid reproduction. This study aimed to introduce principled and efficient methods for the proper management of cockroach control in human dowelling and present the efficiency of these methods. Materials and Methods: A detailed search was carried out on PubMed, Web of Science, Google Scholar, ScienceDirect, Scopus, Medline, and Scientific Information Database databases. The search process was performed using the following keywords: "German cockroach management", "Brown-banded cockroach management", "Integrated pest management", "Urban pest control", "Attractive toxic bait", and "Cockroach resistance". Afterward, duplicate and non-efficient articles were removed and, finally, 66 articles published within 1977-2021 were selected to describe the objectives of this study. Results: Based on the results of published articles in recent years, the best approach to cockroach control is the implementation of programs based on an integrated cockroach control strategy. In this strategy, raising the awareness level of personnel and service forces through training aids and holding training courses has a significant impact on the prevention of cockroach infestation. Among the control methods, the use of formulations with the least toxicity has shown significant efficiency in the control of cockroaches. The use of poisonous sorbent bait, especially in the form of gel, could reduce the cockroach population to zero in less than a week. One of the advantages of this formulation is the targeted use of insecticides, reduction of resistance to insecticides, and minimization of environmental pollution and hazards caused by insecticide residues, which has been considered in the integrated control strategy. Conclusions: Integrated cockroach control-based programs in the form of an "integrated management tactics pyramid" can provide the best performance in controlling cockroach infestation in human habitats.